Altitude training at 2690m does not increase total haemoglobin mass or sea level VO2max in world champion track cyclists - Gore, C. J.; Hahn, A.; Rice, A.; Bourdon, P.; Lawrence, S.; Walsh, C.; Stanef, T.; Barnes, P.; Parisotto, R.; Martin, D.; Pyne, D. (Journal of Science and Medicine in Sport, 1998)
Haemoglobin mass (Hb mass), maximum oxygen consumption (VO2max), simulated 4000 m individual pursuit cycling performance (IP4000), and haematological markers of red blood cell (RBC) turnover were measured in 8 male cyclists before and after (A) 31 d of altitude training at 2690 m. The dependent variables were measured serially after altitude on d A3-4, A8-9 and A20-21. There was no significant change in Hb mass over the course of the study and VO2max at d A9 was significantly lower than the baseline value (79.3 +/- 0.7 versus 81.4 +/- 0.6 ml x kg(-1) x min(-1), respectively). No increase in Hb mass or VO2max was probably due to initial values being close to the natural physiological limit with little scope for further change. When the IP4000 was analysed as a function of the best score on any of the three test days after altitude training there was a 4% improvement that was not reflected in a corresponding change in VO2max or Hb mass. RBC creatine concentration was significantly reduced after altitude training, suggesting a decrease in the average age of the RBC population. However, measurement of reticulocyte number and serum concentrations of erythropoietin, haptoglobin and bilirubin before and after altitude provided no evidence of increased RBC turnover. The data suggest that for these elite cyclists any benefit of altitude training was not from changes in VO2max or Hb mass, although this does not exclude the possibility of improved anaerobic capacity.